Black Market - Patterson, James (HarperCollins Publishers, 1998)
The threat was absolute. At 5.05 p.m. Wall street would be destroyed. No demands, no ransom, no negotiations. A multiple forebombing - orchestrated by a street militia group - would wipe out the financial heart of America. Faced with catastrophe on an unimaginable scale, Federal agent Archer Carroll and Wall Street lawyer Caitlin Dillon are pitched into a heart-stopping race against time, tracking the unknown enemy through a maze of intrigue, rumour and betrayal towards a truly shocking climax...
Keywords: Fiction